2009
DOI: 10.1098/rspb.2009.0417
|View full text |Cite
|
Sign up to set email alerts
|

Heterozygosity-based assortative mating in blue tits (Cyanistes caeruleus): implications for the evolution of mate choice

Abstract: The general hypothesis of mate choice based on non-additive genetic traits suggests that individuals would gain important benefits by choosing genetically dissimilar mates (compatible mate hypothesis) and/or more heterozygous mates (heterozygous mate hypothesis). In this study, we test these hypotheses in a socially monogamous bird, the blue tit (Cyanistes caeruleus). We found no evidence for a relatednessbased mating pattern, but heterozygosity was positively correlated between social mates, suggesting that b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
129
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(142 citation statements)
references
References 67 publications
9
129
4
Order By: Relevance
“…From these recordings, following a procedure similar to that of Johnsen et al (2005), we extracted feeding rates. We found a strong correlation between parental feeding rates estimated with videotape recording and those obtained by means of this system (García-Navas et al 2009). The similarity of the two sets of estimates shows that the PIT-tag method resulted in realistic estimates of provisioning effort.…”
Section: Monitoring Parental Effortmentioning
confidence: 58%
See 1 more Smart Citation
“…From these recordings, following a procedure similar to that of Johnsen et al (2005), we extracted feeding rates. We found a strong correlation between parental feeding rates estimated with videotape recording and those obtained by means of this system (García-Navas et al 2009). The similarity of the two sets of estimates shows that the PIT-tag method resulted in realistic estimates of provisioning effort.…”
Section: Monitoring Parental Effortmentioning
confidence: 58%
“…Another possibility is that such a relationship arises as a consequence of the assortative mating of high-quality birds. In the populations of the Blue Tit we have studied, we have found the heterozygosity of social mates to be positively correlated, suggesting that this species may select mates on the basis of the partner's heterozygosity (García-Navas et al 2009). In addition, in males, we observed a positive association between an individual's genetic diversity and feeding rates.…”
Section: Sex Differences and Effects Of Brood Sizementioning
confidence: 88%
“…Theoretical studies have shown that heterozygosity is heritable when allele frequencies are unequal (Borgia, 1979;Mitton et al, 1993;Neff and Pitcher, 2008), and a number of empirical studies have reported parent-offspring correlations in heterozygosity itself (Cothran et al, 1983;Mitton et al, 1993;Richardson et al, 2004;Hoffman et al, 2007;García-Navas et al, 2009;Oh, 2009;Thoß, 2010;Thonhauser et al, 2014), or inferred them from a parent-offspring correlation in inbreeding coefficients (Reid et al, 2006). Although the presence of substantial heritability of heterozygosity has been formally shown for two-allelic loci more than two decades ago (Mitton et al, 1993), this is not well known among evolutionary biologists (e.g., Coulson and Clegg, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…So far, few studies have considered simultaneously the genetic and phenotypic dimensions of individual quality in relation to pairing patterns in socially monogamous species (but see Freeman-Gallant et al 2003;García-Navas et al 2009;Thünken et al 2012). In particular, heterozygosity can influence body size in vertebrates (Hoffman et al 2010;Herdegen et al 2013), such that patterns of assortative mating in relation to both parameters might be more complex than previously thought.…”
Section: Introductionmentioning
confidence: 99%